REPRESENTASI FOTO PUBLISITAS POLITIK PUAN MAHARANI PADA MAJALAH TEMPO EDISI 19 – 25 SEPTEMBER 2022 (ANALISIS SEMIOTIKA CHARLES SANDERS PEIRCE) - Arvy Verian; Zaki Amrullah; Dian Astari (Journal Publicuho, 2023)
Entering the political year ahead of the 2024 general elections, the public has started to feel the political temperature starting to warm up. This is marked by the start of popping up billboards for political figures who plan to advance in the 2024 general elections. The edition of the Ganjar Miss Puan magazine, September 19-25 2022, revealed how Puan did political publicity. In this tempo magazine it w, as ordered that Ganjar Pranowo's chances of becoming a presidential candidate through the PDI Perjuangan party were almost closed. The door is wide open for Puan Maharani to run as a presidential candidate through the PDI Perjuangan party. Using Peirce's semiotics, there are three trichotomies to analyze photojournalism, namely the first trichotomy of representament consisting of Qualisign, Sinsign, and Legisign. Trichoto is one of the two objects, consisting of icons, indexes, and symbols. Interpretant's third trichotomy consists of Rhema, Decisign, and Argument. Researchers analyzed five journalistic photos in-depth and were analyzed using the three trichotomies. The results of the research show that the 15 – 25 September 2022 edition of Tempo Magazine displays various forms of political publicity strategies carried out by Puan Maharani. This can be seen from most of Puan Maharani's journalistic photos by carrying out pure publicity and free-ride publicity strategies. Puan Maharani also often wears black clothes which means strong and elegant for her.